Bile Acids Reduced the Lipid Deposition in Fatty Degenerated Hepatocytes of Pearl Gentian Grouper (Epinephelus fuscoguttatus♂ × Epinephelus lanceolatus♀) in vitro - Xu, Jia; Yao, Xinzhou; Li, Xiaoyue; Xie, Shiwei; Chi, Shuyan; Zhang, Shuang; Cao, Junming; Tan, Beiping (Frontiers in Marine Science, 2022)
Little is known about the association of bile acids (BAs) with lipid deposition and lipid metabolism of fish in vitro. In the present study, we established the model of fatty-degenerated hepatocytes in pearl gentian grouper (Epinephelus fuscoguttatus♂ × Epinephelus lanceolatus♀), and explored the effects and mechanism of BAs regulating on lipid metabolism in this model. The results showed that fatty-degenerated hepatocytes induced by lipid emulsion accumulated the intracellular triglyceride (TG), the enhanced expression of sterol responsive element binding protein 1 (SREBP1) protein, and the repressed expression of peroxisome proliferator-activated receptor alpha (PPARA), and phosphorylated PPARA (P-PPARA) proteins. BAs co-incubation reduced the content of TG, while increasing the expression of PPARA, farnesoid X receptor (FXR), and G protein-coupled bile acid receptor 1 (TGR5) proteins. Activation of FXR by INT-747 reduced the content of TG, while down-regulating the expression of SREBP1 and PPARA, and up-regulating the expression of P-PPARA, FXR, small heterodimer partner (SHP), and TGR5. Inhibition of FXR by guggulsterone increased the level of TG, while decreasing the expression of TGR5, increasing the expression of SHP. Activation of TGR5 by INT-777 reduced the content of TG, while down-regulating the expression of SREBP1 and SHP, up-regulated the expression of TGR5. Inhibition of TGR5 by SBI-115 elevated the level of TG, while reducing the expression of P-PPARA and TGR5. In conclusion, the FXR and/or TGR5 signaling pathways which were inhibited in fatty-degenerated hepatocytes from pearl gentian grouper, were activated after BAs co-incubation, then altering the lipid metabolism by repressing lipogenesis and enhancing lipolysis, and regulating transcriptional factors, thus reduces the lipid accumulation in vitro.